Seismic Activity Along the Periadriatic and Sava Faults in the Past Two Millennia—An Archaeoseismological Assessment - Miklós Kázmér; Krzysztof Gaidzik (Geosciences)
Most of the Periadriatic Fault System has been active during the Oligocene and Miocene times. Its western part seems to be almost inactive ever since, while the eastern segments show limited seismic activity. We conducted a systematic archaeoseismological survey along the Periadriatic-Sava fault system, assessing buildings and archaeological sites for earthquake damage. Eleven sites, four Roman and seven Medieval, bear evidence of destructive earthquakes which occurred during the past 2000 years. These are (from east to west): Roman Siscia (Sisak) near the Sava fault in Croatia, Roman Celeia (Celje) at the Savinja/Sava faults in Slovenia, Magdalensberg (Roman) just north of the Karavanka fault, Medieval Villach, the Dobratsch landslide and Medieval Arnoldstein at the junction of Mölltal and Gailtal faults, Medieval Millstatt, Sachsenburg. and Roman Teurnia on the Mölltal Fault, Medieval Lienz (all in Austria) and San Candido on the Pustertal fault, as well as Medieval Merano and Tirol (in Italy) adjacent to the North Giudicarie fault zone. Damaged upright walls of Medieval buildings and deformed floors of Roman settlements testify to local intensity up to IX. Ongoing studies of archaeological stratigraphy and construction history allow the dating of one or more seismic events at each site, ranging from the 1st century AD to the 17th century. It is remarkable that the sites, 20 to 70 km apart, along a <400 km long segment of the Periadriatic Fault system, carry evidence for so many high-intensity destructive events, suggesting that the region is tectonically active.